Penerapan Efektivitas Knee-Chest Position Terhadap Rotasi Kepala Janin Trimester III Dengan Letak Sungsang Di Prakter Mandiri Bidan Berkah Kabupaten Wajo - Ariesty AR (Window of Public Health Journal, 2026)
The third trimester of pregnancy is a critical period preceding childbirth, during which the fetal position and presentation greatly determine the success of the delivery process. Breech presentation is a condition in which the fetus is positioned with the buttocks or feet at the lower part of the uterus and the head at the upper part. An uncorrected breech presentation increases the risk of dystocia, a difficult labor process because the presenting part is not the fetal head, which should normally pass through the birth canal. One non-pharmacological intervention that has been proven effective in facilitating fetal repositioning is the knee-chest position, in which the mother kneels with her chest resting on a surface and her pelvis elevated above her head. This study aimed to determine the effectiveness of the implementation of the knee-chest position on fetal head rotation in third-trimester pregnant women with breech presentation at PMB Berkah. This study employed a quantitative approach using a pre-experimental design. The study population consisted of all third-trimester pregnant women with breech presentation who underwent antenatal examinations at PMB Berkah during the study period. The sampling technique used was purposive sampling, in which respondents were selected based on specific criteria relevant to the research objectives. The total sample consisted of 30 respondents. Data were analyzed using univariate and bivariate analyses, with the McNemar test applied for statistical testing. The results showed that 22 out of 30 respondents (73.3%) successfully experienced fetal rotation to a cephalic presentation. The Wilcoxon test yielded a p-value of 0.001, indicating that the knee-chest position had a significant effect on changes in fetal position. Based on these findings, the knee-chest position is a beneficial non-pharmacological intervention that can be implemented in primary midwifery care because it is not only safe but can also be performed independently by pregnant women under the guidance of midwives.